Pathogenicity of H5N8 highly pathogenic avian influenza viruses isolated from a wild bird fecal specimen and a chicken in Japan in 2014. (15th April 2016) - Tanikawa, Taichiro; Kanehira, Katsushi; Tsunekuni, Ryota; Uchida, Yuko; Takemae, Nobuhiro; Saito, Takehiko
ABSTRACT: Poultry outbreaks caused by H5N8 highly pathogenic avian influenza viruses (HPAIVs) occurred in Japan between December 2014 and January 2015. During the same period; H5N8 HPAIVs were isolated from wild birds and the environment in Japan. The hemagglutinin (HA) genes of these isolates were found to belong to clade 2.3.4.4 and three sub‐groups were distinguishable within this clade. All of the Japanese isolates from poultry outbreaks belonged to the same sub‐group; whereas wild bird isolates belonged to the other sub‐groups. To examine whether the difference in pathogenicity to chickens between isolates of different HA sub‐groups of clade 2.3.4.4 could explain why the Japanese poultry outbreaks were only caused by a particular sub‐group; pathogenicities of A/chicken/Miyazaki/7/2014 (Miyazaki2014; sub‐group C) and A/duck/Chiba/26‐372‐48/2014 (Chiba2014; sub‐group A) to chickens were compared and it was found that the lethality of Miyazaki2014 in chickens was lower than that of Chiba2014; according to the 50% chicken lethal dose. This indicated that differences in pathogenicity may not explain why the Japanese poultry outbreaks only involved group C isolates.